Pengaruh Rekrutmen, Seleksi, dan Penempatan Karyawan terhadap Kinerja Karyawan di PT Excellence Qualities Yarn - Inesa Firly Pramestiatama; Anita Oktaviana Trisna Devi (Pusat Riset dan Inovasi Nasional, 2024)
This research is a descriptive quantitative study that calculates and analyzes the effect of recruitment, selection, and job placement on employees at PT Excellence Qualities Yarn. The sample used was 79 respondents with non-probability sampling technique. The data processing method uses multiple linear regression analysis with the F test, T test, and R square test as a statistical research method using SPSS 23. The results showed that there was a simultaneous influence between recruitment, selection, and job placement variables on employee performance. As well as partially obtained that the variables of recruitment, selection, and job placement have a significant effect on employee performance.